Resistant starch production in wheat bread: effect of ingredients, baking conditions and storage - Amaral, Olga (2019)
Resistant starch (RS) is deﬁned as the sum of starch and products of starch degradation not absorbed in the small intestine of healthy individuals. RS appears to confer considerable health benefits. Processing conditions and ingredients may influence the formation of RS in foodstuffs. The aim of the present study was to investigate some of the factors that might influence RS formation in wheat bread, namely: 1) formulation; 2) loaf size; 3) baking conditions and 4) storage conditions. Seven bread formulations were prepared: reference recipe (control) and six experimental formulations. The effect of the loaf size and the baking conditions were also tested. Finally, the effect of storage was tested by keeping control breads under different storage conditions (temperature/time). Moisture and resistant starch contents were evaluated in all breads. A higher level of moisture in the dough and a larger loaf size enhanced the RS content. An extended baking process also favoured significantly the formation of RS. Storing the bread at room temperature for 3 days was shown to further increase the RS content. It is possible to increase the RS content of bread by modifying the ingredients ratio and processing conditions.